Logarithmic Voltage-to-Time Converter for Analog-to-Digital Signal Conversion - Santos, Mauro; Guilherme, Jorge; Horta, Nuno.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents a novel logarithmic conversion architecture based on cross-coupled inverter. An overview of the current state of the art of logarithmic converters is given where most conventional logarithmic analog-to-digital converter architectures are derived or adapted from linear analog-to-digital converter architectures, implying the use of analog building blocks such as amplifiers. The conversion architecture proposed in this book differs from the conventional logarithmic architectures. Future possible studies on integrating calibration in the voltage to time conversion element and work on an improved conversion architecture derived from the architecture are also presented in this book.
Introduction -- Nonlinear A/D Converters -- Proposed Logarithmic ADC -- Logarithmic VTC Design -- Circuit and Layout Level Validation -- Evaluation of the Prototype -- Future Work and Conclusions.
Keywords: Electronic circuits; Signal processing; Electronic Circuits and Systems; Signal, Speech and Image Processing